The Semantics of Biological Forms. (December 2014) - Albertazzi, Liliana; Canal, Luisa; Dadam, James; Micciolo, Rocco
This study analyses how certain qualitative perceptual appearances of biological forms are correlated with expressions of natural language. Making use of the Osgood semantic differential, we presented the subjects with 32 drawings of biological forms and a list of 10 pairs of connotative adjectives to be put in correlations with them merely by subjective judgments. The principal components analysis made it possible to group the semantics of forms according to two distinct axes of variability: Harmony and dynamicity. Specifically, the nonspiculed, nonholed, and flat forms were perceived as harmonic and static; the rounded ones were harmonic and dynamic. The elongated forms were somewhat disharmonious and somewhat static. The results suggest the existence in the general population of a correspondence between perceptual and semantic processes, and of a nonsymbolic relation between visual forms and their adjectival expressions in natural language.